Hospital variations during the first year of the COVID-19 pandemic in a referral hospital in a low-to-middle-income country: a large single-center cohort study - Carmelo Dueñas-Castell; Wilfrido Coronell; Diana Borré-Naranjo; Amilkar Almanza; Leydis Lora Lián; Rafael Navarro; Jose Rojas-Suarez (Revista Ciencias Biomédicas, 2022)
Introduction: to date, few studies reported peak variations in COVID-19 infection in low-and middle-income countries. We aimed to explore the potential reasons for epidemiological changes with time. Methods: this study was conducted at a tertiary referral center in Cartagena, Colombia, between March 7, 2020 and February 28, 2021. Were included adult patients with suspected or confirmed COVID-19. We categorized the study period into two according to the peaks defined in Colombia: the first period included epidemiological weeks 10-35 (March 7, 2020 - August 30, 2020), and the second period included weeks 36-60 (September 1, 2020 - February 28, 2021). We adjusted the mortality by covariates to identify potential changes. Results: in total, 2761 COVID-19 patients were hospitalized. Comparing the two periods, the number of cases was higher during week 21 (peak1: 121 patients) and week 50 (peak2: 128 patients), respectively. The mortality rate declined from 16.5% (95% CI 13.3-19.8) in week 10 to 8.91 (CI 95% 6.95-10.8) in week 60 (p-value <0.001). Conclusions: our study is the first to report a one-year follow-up during the COVID-19 pandemic in a low-and middle-income country. We found a lower mortality rate during the second period, possibly explained by an increase in the experience and a better organization with health resources.